2016
DOI: 10.1101/056317
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Water availability drives signatures of local adaptation in whitebark pine (Pinus albicaulisEnglm.) across fine spatial scales of the Lake Tahoe Basin, USA

Abstract: lis ia 69 of 80 Lind et al: Local adaptation of P. albicaulis 2 Running Title: Local adaptation of P. albicaulis 19 20 ABSTRACT 38 For populations exhibiting high levels of gene flow, the genetic architecture of fitness-related 39 traits is expected to be polygenic and underlain by many small-effect loci that covary across a 40 network of linked genomic regions. For most coniferous taxa, studies describing this 41 architecture have been limited to single-locus approaches, possibly leaving the vast majority of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 108 publications
4
33
0
Order By: Relevance
“…Our understanding of the evolutionary ecology of trees is also shaped by the evolutionary historical context in which comparisons are made. For example, many studies have evaluated local adaptation and the fit of plant phenotypes and genotypes to contemporary environments and climate variation, and have done so within an implicit or explicit framework for the relevant evolutionary history, including species boundaries, hybridization and gene flow (Alberto et al, ; Lind et al, ; Lindtke, Gompert, Lexer, & Buerkle, ; Yeaman et al, ). The evolutionary and historical context for studies of trait variation will determine what processes and dynamics are likely to account for the variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our understanding of the evolutionary ecology of trees is also shaped by the evolutionary historical context in which comparisons are made. For example, many studies have evaluated local adaptation and the fit of plant phenotypes and genotypes to contemporary environments and climate variation, and have done so within an implicit or explicit framework for the relevant evolutionary history, including species boundaries, hybridization and gene flow (Alberto et al, ; Lind et al, ; Lindtke, Gompert, Lexer, & Buerkle, ; Yeaman et al, ). The evolutionary and historical context for studies of trait variation will determine what processes and dynamics are likely to account for the variation.…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of the evolutionary ecology of trees is also shaped by the evolutionary historical context in which comparisons are made. For example, many studies have evaluated local adaptation and the fit of plant phenotypes and genotypes to contemporary environments and climate variation, and have done so within an implicit or explicit framework for the relevant evolutionary history, including species boundaries, hybridization and gene flow (Alberto et al, 2013;Lind et al, 2017;Lindtke, Gompert, Lexer, & Buerkle, 2014;Yeaman et al, 2016). The evolutionary and historical context for studies of trait variation will determine what processes and dy- obtained through DNA sequencing means that some previously intractable relationships between groups can be reconstructed (e.g., Lamichhaney et al, 2015;Martin et al, 2015;McVay et al, 2017;Meier et al, 2017;Wagner et al, 2013) and that sampling of taxa and populations can more comprehensively assay genetic variation near the species level and tie it to evolutionary processes (e.g., Gompert et al, 2014;Mandeville, Parchman, McDonald, & Buerkle, 2015;Parchman, Buerkle, Soria-Carrasco, & Benkman, 2016;Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of elevated islands of divergence in this study, however, does not necessarily indicate an absence of adaptive divergence during speciation with gene flow. The lack of islands of divergence is expected in conifers, given the prevalence of polygenic architectures defining continuous trait variation across species boundaries and the expected prevalence of soft sweeps (Pritchard & Rienzo 2010; Alberto et al 2013; Rajora et al 2016; Lind et al 2017). Alternatively, given the large and complex genomes of conifers (reviewed by De La Torre et al 2014a) our ddRADseq markers underrepresented genic regions, which are often identified as islands of divergence (Nosil & Feder 2012; Zhou et al 2014; Moreno-Letelier & Barraclough 2015; Marques et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We ran ≥5 million iterations following a 500,000‐iteration burn‐in, and we chose the linear BSLMM option except for the case–control phenotype, for which we chose the probit model. Similar to previous work (Lind et al., ), we used the posterior probability of a SNP having a large effect on a phenotype (after accounting for the effects of other SNPs in the genome) to identify candidate genes (see below) because we felt that this metric aptly captured a variant's contribution to that particular trait. SNP counts and sample sizes are given in Table .…”
Section: Methodsmentioning
confidence: 99%